Semi-automatic detection and evaluation of metastases in lymph nodes in diagnostics of the prostate from PET-CT data - Schmidt V.; Spitz L.; Kreißl M.; Saalfeld S.; Genseke P. (Current Directions in Biomedical Engineering, 2024)
We present a novel tool designed for the semiautomatic detection and assessment of prostate cancer during recurrence diagnostics using PET-CT with prostate-specific membrane antigen (PSMA). The tool automatically generates a structured report, which is enhanced by 3D images and ensures the reproducibility of the findings. Moreover, the area of the findings is automatically determined and can be corrected manually. Image data from 50 patients following radical prostatectomy was used. Our approach and its user interface were qualitatively evaluated by a nuclear medicine specialist. The segmentation analysis revealed a requirement for further automation. The resulting report was deemed highly beneficial, particularly in terms of the resulting reproducibility and the presentation of 3D images depicting the findings. The presented tool has great potential for much-needed support in everyday clinical practice, as it facilitates the communication of the diagnostic results to colleagues and patients and thus prevents misunderstandings.